2016
DOI: 10.1186/s12904-016-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

‘I don’t think I’d be frightened if the statins went’: a phenomenological qualitative study exploring medicines use in palliative care patients, carers and healthcare professionals.

Abstract: BackgroundThere is a growing body of evidence suggesting patients with life-limiting illness use medicines inappropriately and unnecessarily. In this context, the perspective of patients, their carers and the healthcare professionals responsible for prescribing and monitoring their medication is important for developing deprescribing strategies. The aim of this study was to explore the lived experience of patients, carers and healthcare professionals in the context of medication use in life-limiting illness.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 23 publications
0
58
2
2
Order By: Relevance
“…The beliefs of caregivers towards deprescribing have been found to be similar, however, acting as a surrogate decision maker is difficult and feelings of guilt and responsibility if their care recipient's condition worsens have been reported [57,59]. Todd and colleagues explored the attitudes of palliative care patients towards medication withdrawal [60]. When patients were accepting of their illness and disease trajectory, they reported placing less importance on their medications and they no longer had fear surrounding ceasing them.…”
Section: Barriers To and Enablers Of Deprescribingmentioning
confidence: 99%
See 1 more Smart Citation
“…The beliefs of caregivers towards deprescribing have been found to be similar, however, acting as a surrogate decision maker is difficult and feelings of guilt and responsibility if their care recipient's condition worsens have been reported [57,59]. Todd and colleagues explored the attitudes of palliative care patients towards medication withdrawal [60]. When patients were accepting of their illness and disease trajectory, they reported placing less importance on their medications and they no longer had fear surrounding ceasing them.…”
Section: Barriers To and Enablers Of Deprescribingmentioning
confidence: 99%
“…Turner et al identified that a polypharmacy cut point of between 3.5 and 6.5 medications predicted negative outcomes in older adults with cancer [104], while Lindsay and colleagues have developed a list of potentially inappropriate medications in this population to support deprescribing activities [105]. Optimising medication use and withdrawal of non-life sustaining medications is a recognised part of palliative care, however, opportunities for reducing polypharmacy are being missed which has led to a renewed focus on deprescribing in palliative care patients [20,60,106].…”
Section: Opportunities For Deprescribing: Special Populationsmentioning
confidence: 99%
“…A qualitative study in the USA to explore palliative care patients’, carers’ and healthcare professionals’ views on stopping unnecessary medications, such as statins, found that patients were accepting of the concept of stopping preventative medications once they had come to terms with the fact that their illness was life-limiting 67. The authors concluded that it was important to explore patients’ expectations of their illness and treatment, and to time discussions about stopping medications appropriately.…”
Section: Barriers and Facilitators To Deprescribingmentioning
confidence: 99%
“…Although lipid-lowering agents may play an anti-inflammatory role, the value of lipid-lowering agents is doubtful among patients with minimal food intake. Similarly, we did not observe a statistically significant change in the prevalence of orders for statins, although emerging research provides evidence of willingness among clinicians, family members and patients to discontinue medications such as statins in palliative care settings 30. A recent randomised trial of continuation of statins versus discontinuation of statins demonstrated that there were no negative consequences to discontinuation of statins in the last months of life 31.…”
Section: Discussionmentioning
confidence: 45%